Factors Affecting The Growth Of Indonesian Shariah Stock Prices (ISSI) With Capital Structure As A Moderating Variable - Mohammad, Fadhel; Haryono, Slamet (INTERNATIONAL JOURNAL OF ECONOMICS AND MANAGEMENT REVIEW, 2024)
Purpose - This study analyzes the factors that affect the growth of Islamic stock prices. It also uses capital structure as a moderating variable to influence this growth. Design/methodology/approach - This study uses purposive sampling, another name for non-probability sampling, as a sample approach. It relied on a sample of 31 companies listed in the Indonesian Sharia Stock Index (ISSI). Moderated regression analysis tests and multiple linear regression analyses are part of the research strategy used in this study. Findings and Discussion - These findings indicate that exchange rate and earning per share variables cannot affect the growth of Islamic stock prices, while return on assets and company size variables can. The capital structure variable cannot strengthen the exchange rate, ROA, EPS, and company size effect on Islamic stock prices.